LITERATURE REVIEW ON ROLE OF TEACHER TRAINING IN IMPLEMENTING TILAWATI METHOD FOR QUR'AN LEARNING - Amir; Rahmad Hakim (As-Sulthan Journal of Education, 2026)
This study aims to review the literature discussing the role of teacher training in the implementation of the Tilawati Method in Qur’an learning across various educational institutions, such as Qur’anic Learning Centers (TPQ) and Quranic schools. Teacher training is a crucial factor in improving the quality of Qur’an instruction, particularly in applying the Tilawati Method, which is systematic and structured. This research employs a qualitative approach through a descriptive-narrative literature review. Data sources consist of relevant scholarly articles and books obtained from academic databases such as Google Scholar, Sinta, Scopus, and ResearchGate, published within the last 10–15 years and written in Indonesian or English. Data analysis was conducted thematically to identify patterns, strategies, effectiveness, benefits, and challenges faced by teachers. The findings indicate that teacher training significantly contributes to enhancing pedagogical competence, understanding of the method, teaching motivation, and the successful implementation of the Tilawati Method in Qur’an learning.